Placebo effect in the treatment of non-small cell lung cancer: a meta-analysis. Issue 3 (8th September 2022) - Ren, Siyuan; Ma, Mengyao; He, Chuan; Deng, Yuhui; Chen, Xiaoyun; Liu, Yonglin; Jin, Yangyang; Liu, Yansong; Cai, Lei; He, Lin
Abstract : Objective: The majority of non-small cell lung cancer (NSCLC) cases remain undiagnosed until advanced stages of the disease. Accumulating studies have highlighted the utility of palliative care as an effective treatment option, which relieves patients' suffering by activating placebo effect in the body. To evaluate the clinical significance of palliative care, data from NSCLC drug-randomized controlled trials (RCTs) were collected and the effects of placebo treatment examined. Methods: PubMed (MEDLINE), Scopus, Web of Science, and China National Knowledge Infrastructure databases were searched from January 1, 1978 to September 1, 2020. Placebo-controlled phase II/III pharmaceutical RCTs enrolling patients with solely stage III/IV NSCLC were included. The quality of included studies was assessed using the Jadad method. Single-arm and two-arm meta-analyses of the therapeutic and adverse effects of placebo, that is, the primary and secondary outcome measures, were subsequently performed using either Bayesian or conventional models. Results: Five RCTs including 2245 drug-treated and 1510 placebo-treated patients at NSCLC stage III or IV were included for the study. Low risk of bias was observed for all five included studies using the Cochrane method. Following placebo treatment, controlled disease rate of 24.1% (95% credible interval [CrI], –0.126–0.609) and dropout rate of 2.1% (95% CrI, 0.007–0.039) were calculated, with a dose reduction rate of 3.0% (95% CrI, 0.017–0.045). Compared with active drug treatment, the placebo treatment group had a risk ratio of 0.81 (95% confidence interval, 0.68-0.97) and 0.85 (95% confidence interval, 0.76–0.96) for the achievement of progression-free survival and overall survival, respectively. Conclusion: In NSCLC drug RCTs, placebo treatment is indicated to generally induce low toxicity in patients by dropout and dose reduction rates and adverse events, although the therapeutic responses could not be precisely determined. The results suggest that under specific circumstances, palliative care which can activate placebo effect may have similar effects as active drugs (such as erlotinib, vandetanib, or pemetrexed) in terms of prolonging survival time.